Counselling the terminally ill — Can we prepare for death? - S. Nieuwmeyer; M. Hosking (South African Family Practice)
The family medical practitioner is a key player when care of the patient becomes palliative. The practitioner's ability to be present to the psychological, spiritual and social needs—in addition to the physical -gives reassurance and affirmation of life up to the point of death. Counselling in the medical field and the approach to opening up a conversation with a patient or family member is discussed.